Faktor Stagnasi Penghimpunan Wakaf Uang Pada LAZ Kota Surabaya - Shabrina Anwari; Muhammad Nafik Hadi Ryandono (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The research aims to discover factors which affected in stagnation of Cash Waqf collection in LAZ Surabaya. Involving three Zakat Institution; YayasanYatimMandiri, Yayasan Dana Sosial Al-Falah, and BaitulMaalHidayatullah. Research method used with qualitative descriptive approach. Data collection has been using with depth interviews and documentation and validation with source-triangulation technique. Analysis technique used is phenomenology qualitative analysis. Research result conveyed as whole practice of Cash Waqf collection used by three of LAZ. Based on analysis by researcher, besides program innovation expert is highly-demands in Cash Waqf for three institutions.Keywords: Cash Waqf, LAZ, Stagnation, Factors, CollectingREFERENCESAbdullah bin Muhammad ath-Thayyar et al. 2006. Ensiklopedia Fiqh Muamalah dalam Pandangan 4 Mazhab. Yogyakarta: Maktabah al Hanif.Abu Abdullah Muhammad ibn Yazid al-QazuwainiwaMajah. Sunan Ibn Maja|h.. Kairo: Mawqi’ Wizarah al-Auqaf al-Mishriyah.Abu Zuhrah, M. 1972. Muhadarat fi al-Waqf. Cairo: Dar al Fikr al-‘Arabi.Al-Asqalāni, Ahmad bin Ali bin Hajar. 1960. Fathu al-Bāri bi SyarhShahīh al-Imām Abi ‘Abdillah Muhammad bin Ismail al-Bukhāri. Juz 6. AlQāhirah: Dār al-Kutub al-Salafiyyah.Al-Hujaili, Abdullah bin Muhammad bin Sa’d. 1999. Al-Auqāf al-Nabawiyyah wa Waqfiyātba’dhi al-Shahābah al-Kirām: DirāsahFiqhiyyah, Tārīkhiyyah, waTstāiqiyyah. Nadwah al-Maktabah al-Waqfiyyah fi al Mamlakah al-‘Arabiyyah al-Su’udiyyah, 25-27 Muharram 1420. Saudi Arabia: Wazāratu al-AuqāfwaSyu’un al-Islamiyyahwa al-Auqāfwa alDa’wahwa al-Irsyād.Al-Jaziri, Abdurrahman. 1970. Kitab Fiqh Ala Mazahib al-Arba’ah. Mesir: Rihayatul Kubra.Al-Mālik, IbnuBathal Abu al-Hasan Ali bin Khalaf bin ‘Abdu. 2003. SyarhShahīh al-Bukhāri li IbniBathal. Juz 6, Cet. 2. Saudi Arabia: Maktabah al-Rusyd.Al-Qasthalani, Ahmad bin Muhammad bin Abi Bakar bin ‘Abdu al-Malik. 1905. Irsyad al-Syāri li al-SyarhShahīh al-Bukhāri. Juz 9, Cet. 7. Mesir: Al-Mathba’ah al-Kubro al-Amiriyah.Al-Syarkhasi, Syamsu al-Din Abu Bakar Muhammad bin Abi Sahl. 2000. AlMabsuth. Juz 12, Cet. 1. Beirut: Dar al-Ma’rifah.Al-Zuhaily, Wahbah. 1985. Al-Fiqh al-Islamiwa Adillatuhu. Juz 8. Damskus:Dar al-Fikr.Azhary, M. Thahir. 2003. Bunga Rampai Hukum Islam Cet. 2. Jakarta: In Hill Co.Azzam, Abdul Aziz Muhammad. 2010. Fiqh Muamalah Sistem Transaksi dalam Fiqh Islam. Jakarta: Amzah.BadanWakaf Indonesia. 2016. PedomanAkuntansiWakaf. Jakarta: Departemen AgamaBank Indonesia. 2016. Wakaf: Pengaturandan Tata Kelola yang Efektif. Jakarta: Departemen Ekonomi dan Keuangan Syariah-Bank Indonesia.Belkaoui, Ahmed Riahl. 2012. Accounting Theory, Fifth Edition. Hampshire: Cengage LearningChowdhury, Md. ShaheedurRahaman, MohdFahmi bin Ghazali, MohdFaisol Ibrahim. 2011. Economics of Cash WAQF management in Malaysia: A proposed Cash WAQF model for practitioners and future researchers.African Journal of Business Management Vol. 5(30), hlm. 12155-12163, 30 November, 2011Dewan Syariah Nasional MUI. 2014. Himpunan Fatwa Keuangan Syariah. Jakarta: PenerbitErlanggaDjunaidi, AchmaddanThobieb Al-Asyhar. 2007. Menuju Era WakafProduktif. Depok: Mumtaz Publishing.Ghozali, Imam dan Anis Chairi. 2007. TeoriAkuntansiEdisi 3. Semarang: Badan Penerbit Universitas Diponegoro.Godfrey, dkk. 2010. Axxounting Theory 7th Edition. New York: John Wiley & Sons.Fanani, Muhyar. 2011. Pengelolaan Wakaf Uang. Vol 9 No 1.Hamdan, Norman, et al. 2013. Accounting for Waqf Institutions: A Review on the Adaptation of Fund Accounting in Developing the Sharia-Compliant Financial Reports for Mosque. [Paper] Presented at World Universities’ Islamic Philanthropy Conference  2013 (WIPCON 2013).Huda, N., &Heykal, M. 2010. Lembaga Keuangan Islam. Jakarta: Prenada Media Group.Ihsan, Hidayatul, et al.Towards The Better Management and Transparency of Waqf Institutions: Lessons from the Charity Commission, UK.Kahf,Monzer. 2000. Al- Waqf Al Islamy: Tatawwuruh,Idaratuh, Tanmiyyatuh.Dasmakus: Dar Al-FikrMardani. 2015. AspekHukum Lembaga Keuangan Syariah di Indonesia. Jakarta: Kencana. Muljono, Djoko. 2015. Buku Pintar Akuntansi Perbankan dan Lembaga Keuangan Syariah. Yogyakarta: Penerbit Andi.N. Campbell. 19.38. “Symposium: measurement and its importance for philosophy,”, Proceedings of the Aristotelian societyNasution, Hasan Mansur. 2010. Wakaf dan Pemberdayaan Umat. Jakarta: Sinar Grafika.Pusat Pengkajian Hukum Islam dan Masyarakat Madani. 2009. Kompilasi Hukum Ekonomi Syariah.  Qāsim, Hamzah Muhammad. 1990. Manār al-QāriSyarhMukhtasharShahīh al-Bukhāri. Juz 4. Damaskus: MaktabahDār al-Bayān.Republik Indonesia. Undang-Undang Nomor 41 Tahun 2004 TentangWakaf. (2015). Jakarta: Diperbanyak oleh Direktorat Pemberdayaan Wakaf.________________.Peraturan Pemerintah Republik Indonesia 42 Tahun 2006 Tentang Pelaksanaan Undang-Undang No. 41 Tahun 2004 Tentang Wakaf. 2015.________________.Peraturan Badan Wakaf Indonesia Nomor 4 Tahun 2010 tentang Pedoman Pengelolaan dan Pengembangan Harta Benda Wakaf.2010. Jakarta: BadanWakaf Indonesia.. Peraturan Menteri Agama Nomor 4 Tahun 2009 tentang Administrasi Pendaftaran Wakaf Uang.2009. Jakarta: MenteriAgamaRahman, A. A. 2009. Peranan Wakaf dalam Pembangunan Ekonomi Umat Islam danAplikasinya di Malaysia. Sharia Journal , Vol 17 No. 1 113-152.Rozalinda. 2016. FikihEkonomi Syariah: Prinsip dan Implementasinya pada Sektor Keuangan Syariah. Jakarta: Raja Grafindo Persada.Rudianto. 2012. Pengantar Akuntansi: Konse pdan Teknik Penyusuna nLaporanKeuangan. Jakarta: Penerbit ErlanggaSabiq, Sayid. 1980. Fiqh as-Sunnah. Libanon: Dar al-FikrSakina, Sri Wahyu dan Latifa Bibi Musafar Hameed. 2014. Conceptual Paper on Qualitative Characteristics: Waqf Accounting in Malaysia. International Conference of Postgraduate Research 2014Sari, Elsi Kartika. 2007. PengantarHukum Zakat  dan Wakaf. Jakarta: GrasindoShihab, M. Quraish. 2002. Tafsir Al-Mishbah. Jakarta: LenteraHatiSoetedjo, Soegeng. 2009. Pembahasan Pokok-Pokok Pikiran Teori Akuntansi Vernon Kam. Surabaya: Airlangga University PressSulaiman, Maliah, MohdAkhyar Adnan dan Putri Nor SuadMegatMohd Nur. 2014. Trust Me! A Case Study of the International Islamic University Malaysia’s Waqf Fund. Review of Islamic Economics, vol. 13, no. 1, 2009, hlm. 69–88.SS Stevens, 1951. Handbook of experimental psychology. New York: John Wiley.Triyuwono, Iwan. 2006. Akuntansi Syariah: Perspektif, Metodologi, danTeori. Jakarta: Raja GrafindoPersada.Tuanakotta, Theodorus M. 1984. Teor iAkuntansi. Jakarta: Lembaga PenerbitFakultasEkonomiUniversitas Indonesia.Yaacob, Hisham, dkk. 2015. Accountability Through Accounting and Reporting Lenses. Humanomics, Vol. 31 Iss. 3 hlm. 299-313.Yin, Robert K. 2014. Case Study Research: Design and Methods Fifth Edition. California: SAGE_____________.2016. Qualitative Research From Start to Finish, Second Edition. New York: The Guilford Press